Collaborative reliance in medicine safety and quality regulation: Investigation of experiences in handling N-nitrosamine impurities among ZaZiBoNa participating countries - Shabangu, Patience P.; Kuwana, Rutendo J.; Dube, Admire (Frontiers in Medicine, 2022)
Introduction: The presence of N-nitrosamine impurities in medicines raised concerns globally as they are genotoxic and probable human carcinogens. A review of N-nitrosamine impurities in medicines provides an opportunity for National Regulatory Authorities (NRAs) to ensure that corrective and preventive actions are applied so that safe and good-quality medicines are made available to the public. This study aimed to investigate the experiences on reviews conducted by NRAs from various Southern African Development Community countries which participate in the regional work-sharing forum, ZaZiBoNa, on the quality and safety data due to the presence of N-nitrosamine impurities in medicines. Methods: A comparative, descriptive study using mixed methods was conducted. Purposive sampling was applied in selecting research participants based on their participation status in the ZaZiBoNa initiative. A standardized questionnaire structured into five parts was completed by ZaZiBoNa focal persons/nominated individuals to determine the experience of each NRA in addressing the safety and quality issues related to the presence of N-nitrosamine impurities in the affected medicines. Profiled medicines included sartans, ranitidine, metformin, rifampicin, and rifapentine. Results: Sartan medicines had been reviewed by all countries participating in the ZaZiBoNa initiative. Although most NRAs have yet to conduct reviews on other profiled medicines, evaluations have been implemented to ensure access to safe and good-quality medicines within the region. Most countries experienced challenges in communicating with applicants or marketing authorization holders (MAHs) on reviewing N-nitrosamine impurities in their medicines. The majority of NRAs agree that there is a need for further collaboration efforts to review N-nitrosamine impurities in medicines. Conclusions: The review of N-nitrosamine impurities in the profiled medicines by NRAs within the region has demonstrated the importance of enhanced regulatory oversight to safeguard against the risks associated with medicines. Collaborative reliance on the review of the safety and quality of medicine, continuous monitoring, implementation and review of processes, testing methods, and regular engagements with stakeholders could be essential in ensuring adequate control of N-nitrosamine impurities in medicines.